Investigation of surface/subsurface integrity and grinding force in grinding of BK7 glass. (June 2017) - Lin, XH; Ke, XL; Ye, H; Hu, CL; Guo, YB
The surface/subsurface integrity and grinding force formed during grinding processes of have been researched on BK7 glass using a surface grinder with diamond grinding wheel. The values of surface roughness, subsurface damage and grinding force were measured and the morphology of surface roughness, and subsurface damage were observed with different grinding parameters. The experimental results show that the values of surface roughness, subsurface damage and grinding force increase with the increasing of feed rate and grinding depth and decreasing of wheel speed. The effects trend of grinding parameters on surface roughness, subsurface damage and grinding force are almost the same and the normal grinding force have great influence on surface roughness and subsurface damage, which agree well with theoretical analysis. These relationships can serve as a useful method for non-destructively predicting subsurface damage depth and a theoretical basis for proposing the appropriate grinding parameters to obtain better surface/subsurface integrity and high efficiency.